The respiratory consequences of COVID-19 lasted for a median of 4 months in a cohort of children aged 2-18 years of age - Doležalová, Karolína; Tuková, Jana; Pohunek, Petr (Acta paediatrica (Oslo, Norway, 2022)
AIM: We focused on the clinical picture, severity and prognosis of children who experienced long-term respiratory issues after COVID-19. METHODS: This was a national Czech multicentre study of paediatric post-COVID syndrome, which used a standard protocol to evaluate structural and functional anomalies and exclude alternative diagnoses. From 6 January to 30 June 2021, 11 paediatric pulmonologists enrolled all paediatric referrals aged 2-18 years with persistent respiratory symptoms more than 12 weeks after COVID-19, namely cough, dyspnoea and chest pain. Medical histories were taken, and physical examinations, lung function testing, chest X-ray and blood tests were performed. RESULTS: The dominant symptoms in the 39 children (56.4% girls) were exertional dyspnoea (76.9%) and a chronic cough (48.7%), while dyspnoea at rest (30.8%) and chest pain (17.9%) were less prevalent. More than half (53.8%) reported more than 1 symptom, and 38.5% had abnormal results for 1 of the following tests: lung function, chest X-ray or D-dimers. The median age of the children was 13.5 years (interquartile range ±4.8 years), and the median recovery time was 4 months (range 1.5-8 months). CONCLUSION: Our initial data suggest that the long-term respiratory impact of COVID-19 was relatively mild in our cohort, with a favourable prognosis.
Keywords: Cough; kašel; mužské pohlaví; coronavirus; Male; Humans; Female; Dyspnea; chronic cough; lidé; COVID-19; dyspnoe; post-COVID syndrome; ženské pohlaví; mladiství; Chest Pain; Child; dítě; SARS-CoV-2; Adolescent; dyspnoea; bolesti na hrudi; Child, Preschool; předškolní dítě